IMPROVING 3D MODEL TEXTURING TECHNIQUES TO ENHANCE REALISM - Karimova , Madinabonu (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This paper examines modern approaches to improving 3D model texturing techniques in order to enhance visual realism. Special attention is given to physically based rendering (PBR), high-resolution textures, procedural material generation methods, and the use of normal, displacement, and reflection maps. The study also analyzes current tools and software solutions widely used in the computer graphics industry, including game engines and visualization systems. As a result, recommendations are proposed for optimizing texturing workflows to achieve higher levels of realism while maintaining performance efficiency. The findings can be applied in video game development, animation, architectural visualization, and other digital content domains.